Exploring the Relationship between Green IT Awareness and Adoption: A Case Study of IT Students in the Gaza Strip - Wessam M. Kollab; Yousef A. Yousef (Jurnal Sistem Informasi, 2023)
Green computing, also known as GIT, has emerged as a crucial field in response to environmental concerns. This study focuses on assessing the level of GIT awareness and adoption among IT students at Al-Aqsa University in Gaza, as well as examining the relationship between GIT awareness and adoption. Data was collected through an online questionnaire completed by 273 participants. The questionnaire covered various aspects of GIT awareness, including understanding, environmental awareness, and e-waste awareness. The collected data was analyzed using statistical techniques such as principal component analysis, mean, and standard deviation. The results indicated that students possessed a satisfactory level of understanding of GIT concepts and the reasons for its adoption. Furthermore, the findings highlighted the significant impact of GIT awareness factors, including GIT understanding, environmental awareness, and e-waste awareness, on GIT adoption. However, it was observed that students did not consistently adhere to GIT guidelines, particularly in terms of frequent internet access and extended computer usage. Interestingly, no significant relationship was found between GIT adoption and students' academic standing. These findings provide valuable insights into the current state of GIT awareness and adoption among IT students and underscore the need for further efforts to promote sustainable computing practices.